2008
DOI: 10.1016/j.cellsig.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin receptor-induced STAT3 phosphorylation in human erythroleukemia cells is mediated via Gαs and Gα16 hybrid signaling

Abstract: 249Introduction: 750

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Additionally, our lab and other investigators have shown that the transcription factor STAT3 plays a key role in late PC by upregulating the expression of cardioprotective proteins such as iNOS, COX-2, HO1, and anti-apoptotic factors [7], [42], [96]. Recent studies in human erythroleukemia cells have shown that IP mediates STAT3 activation by stimulating STAT3 Tyr(705) and Ser(727) phosphorylation [97]. Thus, it appears that IP not only mediates signal transduction for COX-2 but also may act as a facilitator for feedback enhancement of multiple pathways mediating the late phase of PC.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Additionally, our lab and other investigators have shown that the transcription factor STAT3 plays a key role in late PC by upregulating the expression of cardioprotective proteins such as iNOS, COX-2, HO1, and anti-apoptotic factors [7], [42], [96]. Recent studies in human erythroleukemia cells have shown that IP mediates STAT3 activation by stimulating STAT3 Tyr(705) and Ser(727) phosphorylation [97]. Thus, it appears that IP not only mediates signal transduction for COX-2 but also may act as a facilitator for feedback enhancement of multiple pathways mediating the late phase of PC.…”
Section: Discussionmentioning
confidence: 82%
“…The human IP receptor stimulates downstream activation primarily coupled to Gα s -adenylyl cyclase but also has been shown to act through Gq-mediated phospholipase C (PLC) activation [97]. We currently have a good understanding of the structure of IP based on homology modeling with the thromboxane A2 (TP) receptor and the cellular processing of IP from transcription to trafficking [99].…”
Section: Discussionmentioning
confidence: 99%
“…PGI2 signals through G protein‐coupled IP receptors, which, in most cells, couple to G s proteins and activate adenylyl cyclase [25]. To analyse the functional expression of this ligand‐dependent signalling pathway in DCs, we measured cAMP levels.…”
Section: Resultsmentioning
confidence: 99%
“…This mechanism is consistent with investigations invoking both cAMP and cAMPindependent mechanisms in many instances. PROSTAGLANDIN RECEPTORS 507 and STAT3 phosphorylation (Lo et al, 2008), in addition to straightforward analysis of dose-dependent effects on cAMP formation (Accomazzo et al, 2002). PKAmediated switching from G s to G q and/or G i coupling, however, does not seem to be a universal phenomenon (Chow et al, 2003).…”
Section: Ip Receptorsmentioning
confidence: 99%